Risk factors for infection‐related hospitalization in end‐stage renal disease patients during peri‐dialysis period. Issue 4 (19th November 2021) - He, Tianming; Wu, Yuchi; Li, Xiaocui; Yang, Min; Lin, Qizhan
Abstract: Infection‐related hospitalization during the peri‐dialysis period (PDP) in patients with end‐stage renal disease (ESRD) has received less attention. Considering the limited data, we explored the risk factors in this population. Retrospective analysis using the data system to examine factors for infection in ESRD during PDP between January 2012 and December 2017. Patients were divided into infected group and non‐infected group according to the history of infection. Binary Logistic Regression Model was used to search for risk factors. A total of 478 patients were hospitalized during their PDP. One hundred and ninety patients developed infection (39.75%). Thirty‐six patients (18.95%) had two or more infection events, all due to recurrent respiratory infections. The respiratory system was the main site of infection (63.68%), followed by the urinary system and digestive system. Compared with the non‐infected group, the infected group had more patients with hypoproteinemia and coronary heart disease. The following factors: C‐reactive protein >15 mg/L, procalcitonin >1 ng/L, neutrophil percentage >75%, age >52.5 years, platelet >300 × 10 9 /L, neutrophil to lymphocyte ratio, and concomitant coronary heart disease were associated with the occurrence of infection in ESRD patients during PDP. Patients with ESRD have a high incidence of infection during the PDP, with respiratory infection most commonly seen. This research identified several factors associated with risk for infection, which should guide the design of infection prevention strategies.